1997
DOI: 10.1098/rspb.1997.0113
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between frequency–dependent and vertical transmission in host–parasite systems

Abstract: SUMMARYWe investigate host-pathogen dynamics and conditions for coexistence in two models incorporating frequency-dependent horizontal transmission in conjunction with vertical transmission. The first model combines frequency-dependent and uniparental vertical transmission, while the second addresses parasites transmitted vertically via both parents. For the first model, we ask how the addition of vertical transmission changes the coexistence criteria for parasites transmitted by a frequencydependent horizonta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…Number as an alternative to density plays an acknowledged role in disease transmission (Thrall et al 1995;Altizer and Augustine 1997), and its importance in animal behavior is evidenced by discussions of frequency-dependent foraging strategies (Church et al 1996;Marini and Weale 1997;Smithson and Macnair 1997;Allen et al 1998;Belisle 1998). Ecologists have explored effects of group size on survivorship (e.g., Henschel 1998), and commonly demonstrate both costs and benefits of living in groups (reviewed in Radakov 1973;Bertram 1978).…”
Section: Discussionmentioning
confidence: 97%
“…Number as an alternative to density plays an acknowledged role in disease transmission (Thrall et al 1995;Altizer and Augustine 1997), and its importance in animal behavior is evidenced by discussions of frequency-dependent foraging strategies (Church et al 1996;Marini and Weale 1997;Smithson and Macnair 1997;Allen et al 1998;Belisle 1998). Ecologists have explored effects of group size on survivorship (e.g., Henschel 1998), and commonly demonstrate both costs and benefits of living in groups (reviewed in Radakov 1973;Bertram 1978).…”
Section: Discussionmentioning
confidence: 97%
“…High host density can have several effects on disease dynamics. For example, it is most often associated with greater rates of horizontal transmission [5456], leading to localized increases in prevalence. High coral cover reduces the distance between neighboring coral colonies [57] and thus between infected and healthy hosts, increasing the potential for horizontal disease transmission between corals in close proximity.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Altizer et al (2004) found that for females that mated with heavily parasitized males, up to 90% of the progeny were infected for eggs laid immediately (1 day) following mating. Although this percentage declined to zero by 5 days post-mating, mathematical models of host-parasite dynamics indicate that even low rates of paternal transmission can prevent a virulent parasite from going extinct when maternal transmission is high, and hence could be important for explaining parasite persistence in migratory populations, and the high prevalence observed in some resident populations (Altizer and Augustine 1997;Altizer et al 2004).…”
Section: (B) (A)mentioning
confidence: 96%